Pre-launch calibration of the NASA AURA HIRDLS instrument - Barnett, J; Bracken, J; Djotni, K; Hepplewhite, C; Moorhouse, J; Oduleye, O; Palmer, C; Peters, D; Rokke, L; Walton, T; Watkins, R; Whitney, J; et al. (2003)
The High Resolution Dynamics Limb Sounder (HIRDLS) instrument is scheduled for launch on the NASA AURA satellite in January 2004; it is a joint project between the UK and USA. HIRDLS is a mid-infrared limb emission sounder which will measure the concentration of trace species and aerosol, and temperature and pressure variations in the Earth's atmosphere between about 8 and 100 km altitude on a finer spatial scale than has been achieved before. This will depend upon both a high quality of instrument build, and very precise pre-launch calibration. Proto Flight Model calibration was performed in a purpose-built laboratory at Oxford University during an 13-week period in 2002. The tests were made in vacuum under cryogenic conditions close to the space environment. The measurements were divided into spectral, spatial and radiometric, with the HIRDLS pointing capability being used to control which item of test equipment was viewed. A large degree of automation was achieved, and this combined with 24-hour/7-day working enabled a large quantity of information to be obtained.